(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Adyn MF, Sibarani MC, Utoyo L, Surya RA, Sedayu A. 2022. Role of siamang (Symphalangus syndactylus) as seed dispersal agent in a Sumatran lowland tropical forest. Biodiversitas 23: 2101-2110. Seed dispersal is mutualistic interaction between angiosperms and dispersal agents. One of the important dispersers for lowland tropical forests, including in Bukit Barisan Selatan National Park (BBSNP), is siamang (Symphalangus syndactylus Raffles, 1821). This study aimed to determine the seed dispersal pattern, composition of dispersed seeds, and the seed fate dispersed by siamangs at Way Canguk Research Station, BBSNP, Lampung, Indonesia, from February-April 2021. We used the continuous focal sampling method to observe siamang behavior, while the purposive sampling method collected feces and seeds. Siamangs dispersed endozoochory dominantly, all fecal contained seeds, deposited more in the morning, and more scattered than clumped. With a gut passage time of 22.5 ± 3 hours, the seed dispersal distance was 223.9 ± 142 meters from the parents. Seeds < 3 mm were more numerous, but seeds > 3 mm were dispersed more often. Siamang was recorded to disperse a mean of 3.3 ± 1.4 species/feces, and 22 species were dispersed. The germination test showed that only 28% of total planted seeds successfully germinated. Based on in situ monitoring, the remaining deposit sites only accounted for 12% of total records, while the germination rate of dispersed seeds from these deposit sites varied. Further studies are needed with a larger sample to test the consistency of these findings.